Tidak ada PENGUATAN ETIKA WARGA DIGITAL DI KALANGAN PRIA GEN Z DI JAKARTA BERBASIS NILAI PANCASILA - Belva Gerrya Putri Juneva, Belva (Lentera Ilmu Madani, 2025)
This study aims to analyze digital ethics awareness among Gen Z males in Jakarta by positioning Pancasila values as the main moral foundation. Phenomena such as hate speech, cyberbullying, and the spread of hoaxes indicate a degradation of ethical values influenced by digital environments and permissive social interactions. A qualitative method was employed through semi-structured interviews with four Gen Z males who are active users of social media in Jakarta. The findings reveal that although the respondents understand the importance of digital ethics and recognize Pancasila as a relevant moral guide, its application remains individual and lacks systematic integration. Factors such as peer influence, family, and educational content on social media significantly shape their ethical awareness and behavior. Therefore, strengthening digital ethics based on Pancasila values is considered crucial for fostering digitally responsible, civilized, and morally grounded youth in alignment with national identity.